Does tourism contribute towards zero-carbon in Australia? Evidence from ARDL modelling approach. (September 2022) - Avishek Khanal,; Rahman, Mohammad Mafizur; Khanam, Rasheda; Velayutham, Eswaran
Abstract: Climate change is an increasingly serious problem, resulting in significant environmental degradation, and various policies and regulations have been adopted to achieve zero-carbon with the goal of ameliorating this issue. To end this, along with economic growth, governments should consider human activities such as tourism and energy consumption, which are responsible for raising CO2 emissions, a proxy for environmental degradation, in the atmosphere. Tourism may contribute to climate change through various adverse activities such as transportation and hotel stays. Thus, this study investigates the long-run cointegrating relationship between tourism and environmental degradation, focusing on some other specific factors. Using data from 1976 to 2019, the autoregressive distributed lag bounds test approach is applied to obtain both long-run and short-run coefficients. The estimated results indicate that tourism obstructs the achievement of zero-carbon in Australia. Along with tourist arrivals, energy consumption and gross domestic product are also significant contributors which have a positive and statistically significant long-run relationship with carbon emissions. This study provides policy implications for zero-carbon and sustainable tourism growth in Australia. Highlights: Climate change is an increasingly serious issue, resulting in environmental degradation. Investigates the tourist arrivals and CO2 emissions nexus. Results show tourism has significant impact on the environment and is barrier to achieve zero-carbon. Energy consumption and GDP are also significant contributor to the CO2 emissions. Policy considerations are proposed.